Keputusan Administrasi Negara (Beschikking) - Erliyana, Anna (Pelita Harapan University, 2005)
Adiministrative decision made by government, legally called administrative Decree (Ketetapan Aministrasi), is a decision issued by the authority in order to give legal basis for all administrative actions of public agencies. Not only that, such Decree is also the rules of procedure or code of conduct upon which every state of government agencies conduct their interrelation and cooperation. The competence vested within its organs agencies, which in turn also serves as the source of law for those agencies to operate. A Decree issued by an Agency not given the legal authority is considered invalid that is, null and void.